Volume 5A: Heat Transfer 2019
DOI: 10.1115/gt2019-90458
|View full text |Cite
|
Sign up to set email alerts
|

Aerothermal Simulations Comparisons of a Shaped-Hole Film Cooling Flow

Abstract: Film Cooling is a crucial technology for engine manufacturer to develop high-efficiency gas turbine engines by raising turbine entry temperature. A lot of cooling holes geometries have been studied in the past few years in tests, as well as numerical simulations. Shaped holes are nowadays a standard geometry for protecting the blades, given the performance improvement compared to cylindrical holes. Numerical correlation with physical tests is challenging due to the high sensitivity to thermal mixing and adequa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…To better assess the relative performances of the different models, Figure 12 details the centerline effectiveness distributions for the different models. As already mentioned before, Simon et al [33] have shown that conductive effects not taken into account in the RANS and LES simulations are responsible for the most part of the discrepancy between LES and experiment. Therefore, RANS results are to be compared more to the LES evaluation than to experimental results, both of them assuming adiabatic boundary conditions.…”
Section: Rans Simulationsmentioning
confidence: 87%
See 1 more Smart Citation
“…To better assess the relative performances of the different models, Figure 12 details the centerline effectiveness distributions for the different models. As already mentioned before, Simon et al [33] have shown that conductive effects not taken into account in the RANS and LES simulations are responsible for the most part of the discrepancy between LES and experiment. Therefore, RANS results are to be compared more to the LES evaluation than to experimental results, both of them assuming adiabatic boundary conditions.…”
Section: Rans Simulationsmentioning
confidence: 87%
“…For 𝑍/𝐷 = ±3 the effectiveness is zero for the LES, whereas it does not vanish in the experimental data (Figure 6). Simon et al [33] have shown that this discrepancy can be explained by the conductive heat transfer within the plate, not reproduced by the adiabatic wall boundary condition of the simulation. Note also that to investigate dynamic Reynolds-stress models, taking into account heat conduction within the plate would not be relevant.…”
Section: The Computational Domain Of the Les Represented Inmentioning
confidence: 97%
“…Although limited research has been able to predict adiabatic effectiveness along the hole centerline, conventional Reynolds-averaged Navier-Stokes (RANS) turbulence models have been shown to be inadequate in capturing the lateral spreading of the jet in crossflow [4] [5] [6]. Recent work has also explored the use of a Lattice-Boltzmann solver to capture the turbulent flow physics for both adiabatic and conjugate heat transfer cases [7] [8]. With all things considered, some form of a scale-resolving simulation with a subgrid-scale model is desired in order to accurately predict the effectiveness of film cooling schemes.…”
Section: Introductionmentioning
confidence: 99%